A research on the surface morphology, microstructure evolution and wear property of selective laser melting Al2O3/P20 composites. (17th January 2020) - Lin, Zhixiong; Zhang, Xiaoxun; Ma, Fang; Chen, Chuanbo; Dong, Sensen; Jiang, Juze; Yang, Wei
Abstract: The Al2 O3 /P20 composites were successfully manufactured by selective laser melting (SLM) from powder mixture of Al2 O3 and P20 mold steel with different Al2 O3 contents (0.5 wt%, 1 wt%, 2 wt%) in this work. The surface morphology analysis indicated that Al2 O3 particles were partially or fully melted for agglomerates during the SLM process with segregating between contiguous molten tracks. The model of Al2 O3 diffusing during the SLM process was built for illustrating the generated mechanism of Al2 O3 agglomerates. Moreover, the densification behavior of specimens became poor (the relative density declined from 99.3% to 94.2%) as the Al2 O3 contents increased. The microstructure within samples had some obvious variations including coarsening martensite microstructure, tempering microstructure transformation, reverted austensite and precipitation of fine carbide particles. The result of Rockwll hardness test manifested that 1 wt% obtained the maximum value of 57.6 HRC, while 2 wt% had the minimum value of 45.9 HRC. Tribological test revealed that coefficient of friction (COF) and wear rate significantly declined when the Al2 O3 contents were 1 wt% and 2 wt%, which emphasized the superior wear resistance property.